KONSTRUKSI INDEKS KESTABILAN SISTEM KEUANGAN INDONESIA - Anhar Fauzan Priyono (Universitas Negeri Medan, 2017)
Financial system stability is necessary to ensure a sustainable economic development. It undertakes 3 major functions: (i) payment system, (ii) financial intermediation, and (iii) managing risk. Data showed that the Indonesian economy experienced a negative correction in the event of financial instability, e.g bank panic in 1992, Asian financial crisis (1997), and Sub-prime mortgage crisis (2008). Therefore, it is necessary in having a method of financial stability index measurement, which in turn can be used to predict the direction of future financial stability. This research was conducted in order to provide an option incalculating the index of financial stability of Indonesia by two methods, namelyAggregation with Variance Equal Weight with Principal Component Analysis (PCA). The results show that the trend of Indonesian financial stability index which constructed through these two techniques have similar trend with a different magnitude. PCA method was employed in making reductions on variable dimensions without losing the information on the movement of the variable’s variation. There are four sectors to be included in the index. Those four sectors are banking sector, money market sector, capital market sector,and monetary sector. We found that the contribution of the financial performance of banks in Indonesia and the interest rate is the highest among other sector to the Indonesia financial stability.